Indonesia and the law of the sea - Hasjim, Djalal (Centre for strategic and international studies (CSIS), 1995)
To study the lainkages between the new international economic order and the law of the sea, two aproach should necessarily be pointed out. First, a carefull analysis of the single negotiating text produced by the law of the sea (LOS) conference is needed to understand its infact on in the new internatioanl economic order (NIEO). second, the documents of the sixth and seventh special sessions of the general assembly and the charter of economic rights and dutis of states have to examined to establish in what areas they make demands, explicitly or omplicitly, on the law of the sea conference.